2019
DOI: 10.1080/13102818.2019.1568913
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of 17β-estradiol and products by a mixed culture of Rhodococcus equi DSSKP-R-001 and Comamonas testosteroni QYY20150409

Abstract: In this study, we investigated environmental oestrogen 17b-estradiol (E2) degradation by a mixed culture of Rhodococcus equi DSSKP-R-001(RS) and Comamonas testosteroni QYY20150409(CT). The results demonstrated that the two strains exhibited synergistic E2 degradation activity, showing that multispecies bacterial systems can improve microbial survival and activity. The E2 degradation rate for the mixed culture system was 94% under conditions in which E2 was the sole source of carbon and growth energy, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…Although many detailed estrogen degradation pathways have been proposed [9,27,41], studies on the intracellular metabolism of estrogen have not been reported. At the same time, estrogen pollution is currently caused by multiple channels and multiple estrogens, and the study of bacterial estrogen degradation therefore has great practical significance.…”
Section: Introductionmentioning
confidence: 99%
“…Although many detailed estrogen degradation pathways have been proposed [9,27,41], studies on the intracellular metabolism of estrogen have not been reported. At the same time, estrogen pollution is currently caused by multiple channels and multiple estrogens, and the study of bacterial estrogen degradation therefore has great practical significance.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria that degrade these hormones belong to genera such as Bacillus , Virgibacillus , Novosphingobium , Rhodococcus , Acinetobacter , Pseudomonas , Sphingomonas , Enterobacter , Klebsiella , Aeromonas , Comamonas , Thauera , Deinococcus , Stenotrophomonas and cyanobacteria [ 3 , 4 , 6 , 7 , 10 , 12 , 25 , 28 , 31 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Raphidocelis subcapitata , Chlorella vulgaris , Chlorococcus and Scenedesmus quadricauda belong to algae capable of removing hormones [ 11 , 26 , 40 , 41 ].…”
Section: Microbiological Degradation Of Edcsmentioning
confidence: 99%
“…In addition, 17β-estradiol is usually degraded faster while estrone and synthetic estrogens are decomposed slower [ 34 , 47 ]. Moreover, Wang et al [ 37 ] noted the synergistic effect of mixture strains during 17β-estradiol degradation. While individual strains degraded to 86% of the hormone, the mixture of strains almost completely degraded 17β-estradiol.…”
Section: Microbiological Degradation Of Edcsmentioning
confidence: 99%
See 2 more Smart Citations